RELATIVE CLAUSE AND ITS TRANSLATION FOUND IN “THE GOOD EARTH”: RELATIVE CLAUSE AND ITS TRANSLATION FOUND IN “THE GOOD EARTH” - I Made Juliarta (Focus Journal : Language Review, 2022)
This research study focuses on English relative clauses and its translations into Indonesian found in the story entitled “The Good Earth”. This study aims to: (i) analyze the types of relative clauses found in the data source, (ii) analyze the types of translation in the translation process from source language into target language. The research study applied the theory of relative clauses proposed by Quirk (1985), Sneddon (1996) and the theory of translation shift which was proposed by Catford (1965). The process of collecting data is started by reading the entire data source in order to understand the story and observe the possibility of the data source which could be taken from the data source. The data source was read to find out the types of English relative clauses which were found in the story in the method and technique of collecting the data. The research study found that one type of English relative clauses was found in the story entitled “The Good Earth”. It was the type of Restrictive relative clause found in the novel entitled “The Good Earth”. First, it can be seen that the types of English relative clauses found in the data sources are called as restrictive relative clause as subject, restrictive relative clause as object, restrictive relative clause as prepositional object, non-restrictive relative clause as subject, and non-restrictive relative clause as object. Secondly, there are two types of translation strategies used in translating from source language into target language.